Theoretical Study of the Reaction Mechanism and Kinetics of HO2 with XCHO (X = F, Cl). Issue 2 (15th December 2016) - Long, Bo; Tan, Xing‐Feng; Bao, Junwei Lucas; Wang, Ding‐Mei; Long, Zheng‐Wen
ABSTRACT: The reactions of HO2 with FCHO and ClCHO have been theoretically investigated by combining beyond‐CCSD(T) electronic structure benchmarks, validated density functional theory, and canonical variational transition state theory with small‐curvature tunneling, coupled‐torsions anharmonicity, and high‐frequency anharmonicity. This investigation explores three different reaction mechanisms: radical addition plus a hydrogen transfer, radical addition, and hydrogen abstraction. The calculated results show that the dominant reaction pathway is the terminal oxygen atom of HO2 added to the carbon atom of XCHO (X = F, Cl) and simultaneously the hydrogen atom of HO2 transferred to the oxygen atom of the C=O group in XCHO. The reaction barriers of the other reaction pathways are so high that these processes are negligible in the atmosphere. Although the barrier height of the dominant reaction pathway in the HO2 + FCHO reaction is 0.61 kcal/mol higher than that of the corresponding HO2 + ClCHO reaction, the HO2 + FCHO reaction is faster than the HO2 + ClCHO reaction because the variational effects of HO2 + ClCHO is more obvious than that of the HO2 + FCHO. The present results show that the HO2 + FCHO reaction may be important in the atmosphere. The present results should be useful in evaluating the atmospheric fate of XCHO (X = F, Cl).